MAXIMIZING BRAND EXPOSURE IN THE 21ST CENTURY; BRANDING AS A STRATEGY FOR CREATING COMPETITIVE EDGE - Julius Tapera (International Journal of Research Science and Management, 2015)
This paper examines branding as a marketing concept and how organizations can explore it for creating competitive advantage. It defines branding and explores the various aspects that organizations can pay attention to, in marketing either their products or services, in making their brands distinct. Product features and benefits, company logos, corporate wear, unique ambience and exquisite office furniture are some among the key aspects that various organizations can exploit to create cutting edge brands that would distinguish their organizations, products and services from the rest of the players in their respective industries. Branding objectives, elements of branding, types of brands, branding strategies and principles of brand strategy are the key concepts covered in this paper. The use of social media in exposing your brand is also discussed in this paper.